Efektifitas Berpikir Kreatif Siswa ditinjau dari Koneksi Matematis dalam Pemecahan Masalah Siswa Kelas VIII SMP Negeri 7 Buton Tengah - Rahmatia Rahmatia; Abdurahman Askois; Ilman Ilman (Jurnal Akademik Pendidikan Matematika, 2022)
The problem in this research was whether creative thinking was effective reviewed from the mathematics connection in solving problem at SMP Negeri 7 Buton Tengah. The objective of this research was to know the effectiveness of students’ creative thinking reviewed from the mathematics connection in solving problem at SMP Negeri 7 Buton Tengah. This research was experimentalresearch. Population in this research was all grade VIII SMP Negeri 7 Buton Tengah. Sample in this research was taken by using random sampling technique with 44 students consisted of class VIII A as experimental class and VIII B as control class in which each classes consisted of 22 students. Instrument used in this research was test. Research outcome obtained showed that: (1) the result of students’ mean score in pre-test in experimental class was 66.59, while in control class was 62.27. (2) the result of students’ mean score in post-test in experimental class was 80.45, while in control class was 70.68. From hypothesis test result by using t-test, obtained t-count = 3.403 and significant value p = 0.039. Therefore, it could be concluded that students’ creative thinking reviewed from the mathematics connection in solving problem was effective at grade VIII in SMP Negeri 7 Buton Tengah.